2015
DOI: 10.1001/jama.2015.4559
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Aflatoxin With Gallbladder Cancer in Chile

Abstract: In Chile, gallbladder cancer is a leading cause of cancer death in women. Other than gallstones, gallbladder cancer etiology remains largely unclear. Exposure to aflatoxin, a liver carcinogen, is associated with bile duct epithelium proliferation in both animals and humans, 1 and with gallbladder cancer in primates. 1 Aflatoxin contamination has been identified in Chile, including in ají rojo (red chili peppers). Ají rojo is associated with gallbladder cancer 2 ; however, the association of aflatoxin with gall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 3 publications
3
50
0
2
Order By: Relevance
“…For example, aflatoxin B1 (AFB1) exposure leads to specific somatic mutations in TP53 , with a high frequency of transversions at codon 249 [28], and animal studies have found that AFB1 exposure leads to increased pro-inflammatory cytokine and regulatory cytokine expression while decreasing lymphocyte proliferation [29,30]. A recent short report found that GBC cases were 13 times more likely to have detectable circulating aflatoxin-albumin adducts than normal controls (OR, 13.2; 95% CI, 4.3–47.9) [31]. While the finding needs to be replicated in other studies, it is of interest because of the link between aflatoxin, TP53 mutations, and inflammation.…”
Section: Inflammation and Cancermentioning
confidence: 99%
“…For example, aflatoxin B1 (AFB1) exposure leads to specific somatic mutations in TP53 , with a high frequency of transversions at codon 249 [28], and animal studies have found that AFB1 exposure leads to increased pro-inflammatory cytokine and regulatory cytokine expression while decreasing lymphocyte proliferation [29,30]. A recent short report found that GBC cases were 13 times more likely to have detectable circulating aflatoxin-albumin adducts than normal controls (OR, 13.2; 95% CI, 4.3–47.9) [31]. While the finding needs to be replicated in other studies, it is of interest because of the link between aflatoxin, TP53 mutations, and inflammation.…”
Section: Inflammation and Cancermentioning
confidence: 99%
“…An association has also been found between gallbladder cancer and the aflatoxins present in grain-based agriculture as well as the ochratoxin A in red peppers. This association has been seen in the population of Amerindian ancestry in Chile that consumes them frequently as well as in the Peruvian and Bolivian population [19, 20, 21]…”
Section: Discussionmentioning
confidence: 87%
“…The level of aflatoxin-albumin adducts was used as a substitute measurement for exposure, and was compared between GbCa patients and two sets of controls either with or without gallstones. The presence of aflatoxin adducts was significantly more frequent in patients with gallbladder disease, and levels of adducts were higher in the patients with GbCa (median value 7.6 pg/mg of albumin) compared to aflatoxin-positive gallbladder controls (3.5 pg/mg of albumin) and community controls without gallstones (2.4 pg/mg of albumin) [35]. These data suggest a role for carcinogenic contaminants in the diet and warrants closer examination of food contaminants in other populations with a higher incidence of GbCa.…”
Section: Environmental Risk Factors For Gallbladder Cancermentioning
confidence: 92%
“…24 No 3: 339-348 Aymara and Chechua Indios in Bolivia [34] and in Chile [7]. A recent study reported a potential association of aflatoxin contamination in ají rojo (red chili peppers) with GbCa in Chile [35]. Aflatoxin is a liver carcinogen associated with bile duct epithelium proliferation in humans and animals.…”
Section: Environmental Risk Factors For Gallbladder Cancermentioning
confidence: 99%